Timor Leste - Issues and Options in the Household Energy Sector : A Scoping Study - World Bank (Washington, DC, 2012)
The important role of biomass fuels today. Timor Leste is a relatively small country located in the eastern part of Timor Island with an area of about 1.5 million ha and an estimated 2007 population of 1.0 million. At about US$550 GDP per capita, it is one of the least developed countries in the world, with an estimated 40 percent of the population in poverty. However, the development of offshore oil and gas resources in partnership with Australia has recently begun to generate substantial revenues for the Government. The country still faces huge challenges ahead, as it tries to rebuild an economy that was totally devastated during the recent periods of violence and civil unrest. In the energy sector, several major investment projects have been initiated that would greatly expand the power generation and distribution infrastructure, and make electricity accessible to large numbers of currently un-served urban and rural people. For the household sector, there is no question that improved access to electricity will dramatically improve the quality of life, through superior electric lighting and the capability to use modern, more efficient appliances. Electricity, however, is unlikely to make even a dent in the vast majority of homes as a substitute for other cooking fuels.